2007
DOI: 10.1155/2007/342618
|View full text |Cite
|
Sign up to set email alerts
|

Symposium on Obesity and Asthma –November 2, 2006

Abstract: Asthma and obesity are frequently associated, and obesity has been considered a factor contributing to both an increase in severity of asthma and to its development. The present document summarizes the proceedings of a symposium held in Montreal, Quebec, on November 2, 2006, under the auspices of the Réseau en santé respiratoire du Fonds de la recherche en santé du Québec in collaboration with the McGill University - Strauss Severe Asthma Program, Université Laval (Quebec City) and Université de Montréal. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 87 publications
1
19
0
1
Order By: Relevance
“…First, it is associated with an upper airway inflammatory process that has the potential to influence lower airways. In this regard, significant systemic and upper airway inflammation has been reported with OSA [106,107], and Devouassoux et al reported bronchial neutrophilia and a high IL-8 concentration in patients with untreated OSA compared with controls [108].…”
Section: Obstructive Sleep Apneamentioning
confidence: 98%
See 1 more Smart Citation
“…First, it is associated with an upper airway inflammatory process that has the potential to influence lower airways. In this regard, significant systemic and upper airway inflammation has been reported with OSA [106,107], and Devouassoux et al reported bronchial neutrophilia and a high IL-8 concentration in patients with untreated OSA compared with controls [108].…”
Section: Obstructive Sleep Apneamentioning
confidence: 98%
“…Continuous positive airway pressure treatment of OSA, in patients with asthma, improved asthma symptoms, rescue broncho dilator use, peak expiratory flows and asthma-specific quality of life [107,116]. Lafond et al found, however, no significant changes in airway responsiveness after 6 weeks of nocturnal continuous positive airway pressure treatment, while patients' asthma-related quality of life improved [116].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…114,122 Fewer studies have reported spirometric outcomes in lean and obese children with asthma. Unlike in adults, obesity does not appear to reduce vital capacity or total lung capacity substantially, 98,104,106,109 and in some reports may be associated with greater volumes and capacity.…”
Section: Lung Functionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) treatment of OSA in patients with asthma improves outcomes, including asthma symptoms, [7][8][9] rescue bronchodilator use, 7 peak expiratory flow rates (PEFRs), 7 and asthma-specifi c quality of life assessed with validated instruments. 10,11 Although important, these studies included small numbers of participants selected primarily for nocturnal symptoms and used nonrandomized designs. Additionally, OSA was recently identifi ed as an important risk factor for frequent exacerbations in patients with diffi cult-to-treat asthma.…”
mentioning
confidence: 99%